Association of parental history of type 2 diabetes with age, lifestyle, anthropometric factors, and clinical severity at type 2 diabetes diagnosis: results from the DD2 study. Issue 3 (6th November 2015) - Svensson, Elisabeth; Berencsi, Klara; Sander, Simone; Mor, Anil; Rungby, Jørgen; Nielsen, Jens Steen; Friborg, Søren; Brandslund, Ivan; Christiansen, Jens Sandahl; Vaag, Allan; Beck‐Nielsen, Henning; Sørensen, Henrik Toft; et al.
Abstract: Background: We investigated whether parental history of type 2 diabetes mellitus (T2D) is associated with age, lifestyle, anthropometric factors, and clinical severity at the time of T2D diagnosis. Methods: We conducted a cross‐sectional study based on the Danish Centre for Strategic Research in Type 2 Diabetes cohort. We examined the prevalence ratios (PR) of demographic, lifestyle, anthropometric, and clinical factors according to parental history, using Poisson regression adjusting for age and gender. Results: Of 2825 T2D patients, 34% ( n  = 964) had a parental history of T2D. Parental history was associated with younger age at diagnosis [adjusted (a)PR 1.66, 95% confidence interval: 1.19, 2.31) for age <40 years; aPR 1.36 (95% confidence interval: 1.24, 1.48) for ages 40–59 years] and with higher baseline fasting plasma glucose [≥7.5 mmol/L, aPR 1.47 (95% confidence interval: 1.20, 1.80)], and also tended to be associated with lower beta cell function. In contrast, patients both with and without a parental history had similar occurrence of central obesity [91% vs. 91%], weight gain ≥30 kg since age 20 [52% vs. 53%], and lack of regular physical activity [60% vs. 58%]. Presence of diabetes complications or comorbidities at T2D diagnosis was not associated with parental history. Conclusions: The lack of an association between parental history and adverse lifestyle factors indicates that T2D patients do not inherit a particular propensity for overeating or inactivity, whereas patients with a parental history may have more severe pancreatic beta cell dysfunction at diagnosis. Copyright © 2015 John Wiley & Sons, Ltd.